(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
crime in the field of information technology (IT) is rapidly developing - the number of cyber-attacks, fraud, and theft of personal information is increasing. Legal education and legal clinics are finding their place among the measures against such crimes.